Influence of flame-generated ions on the simultaneous charging and coagulation of nanoparticles during combustion. Issue 7 (3rd July 2017) - Wang, Yang; Sharma, Girish; Koh, Clement; Kumar, Vivek; Chakrabarty, Rajan; Biswas, Pratim
ABSTRACT: Flames generate a large amount of chemically and thermally ionized species, which are involved in the growth dynamics of particles formed in flames. However, existing models predicting particle formation and growth do not consider particle charging, which may lead to bias in the calculated size distribution of particles. In this study, Fuchs' charging theory was coupled with a monodisperse particle growth model to study the simultaneous charging and coagulation of nanoparticles during combustion. In order to quantify the charging characteristics of nanoparticles, a high-resolution DMA was used to measure the mobilities of ions generated from a premixed flat flame operated at various conditions. The effect of temperature on ion–particle and particle–particle combination coefficients was further examined. The proposed model showed that the influence of charging on particle growth dynamics was more prominent when the ion concentration was comparable to or higher than the particle concentrations, a condition that may be encountered in flame synthesis and solid fuel-burning. Simulated results also showed that unipolar ion environments strongly suppressed the coagulation of particles. In the end, a simplified analysis of the relative importance of particle charging and coagulation was proposed by comparing the characteristic time scales of these two mechanisms. © 2017 American Association for Aerosol Research